2016
DOI: 10.1093/bioinformatics/btw041
|View full text |Cite
|
Sign up to set email alerts
|

BioCircos.js: an interactive Circos JavaScript library for biological data visualization on web applications

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 9 publications
0
83
0
Order By: Relevance
“…The transcriptIDs can be used to cross-reference with Supplemental Data 2 which is a GFF transcript annotation file that contains exon structure for each TE transcript. All TEs and "ExpressedAndAnnotated" TEs are used in the circular BioCircos plot (Cui et al, 2016) shown in Figure 2B.…”
Section: Updating the Tair10 Te Annotationmentioning
confidence: 99%
“…The transcriptIDs can be used to cross-reference with Supplemental Data 2 which is a GFF transcript annotation file that contains exon structure for each TE transcript. All TEs and "ExpressedAndAnnotated" TEs are used in the circular BioCircos plot (Cui et al, 2016) shown in Figure 2B.…”
Section: Updating the Tair10 Te Annotationmentioning
confidence: 99%
“…A related tool, MultiProtScale (Table 2), computes and displays physicochemical properties of amino acids over sequences and alignments, acting as an interactive extension of Expasy's ProtScale tool. Moving on to genomics, SnipViz [32] and BioCircos.js [33] help visualize and disseminate gene and protein sequences and their annotations, while GenomeD3Plot [34] and pileup.js [35] allow for interactive in-browser visualization of genomic data.…”
Section: Javascript Libraries For Online Interactive Data Displaymentioning
confidence: 99%
“…A related tool, MultiProtScale (Table 2), computes and displays physicochemical properties of amino acids over sequences and alignments, acting as an interactive extension of Expasy's ProtScale tool. Moving on to genomics, SnipViz [32] and BioCircos.js [33] help visualize and disseminate gene and protein The cleaned text is then processed with nlp-compromise to calculate frequencies of words and n-grams (word pairs, triplets, etc. ); (C) Example interactive visualization of an alignment of PFAM seed members for COX2 (PF00116) with JSAV [3], achieved through the demonstration webpage at http://www.bioinf.org.uk/software/jsav/.…”
Section: Javascript Libraries For Online Interactive Data Displaymentioning
confidence: 99%
“…The server frontend is designed using the Bootstrap css framework. The interactive display of the mutation data relies on BioCircos.js (16) and Cytoscape.js (17) javascript libraries, which were modified to fulfill the visualization needs. D3.js (https://d3js.org/) javascript library is also used to display legend information, and Jsmol (http://www.jmol.org/) to provide interactive visualization of protein 3D structures.…”
Section: Server Informationmentioning
confidence: 99%